Medical and Social Aspects of Reproductive Health of Children Aged 8 to 15 Years - Egamberdieva Gulnora Nematovna (Genius Journals, 2022)
In conditions of social tension and stratification of society, a sharp drop in the standard of living of the population, it is children and adolescents who become one of the most vulnerable groups of the population. But it is adolescents who are the reproductive, intellectual, economic, social, political and cultural reserve of society. This determines the huge social significance of their health
Keywords: Reproductive health; sex education; adolescents; risk factors